Pengaruh Pijat Bayi Terhadap Kualitas Tidur Bayi di Puskesmas Wilayah Kabupaten Gowa : The Effect of Baby Massage on Baby Sleep Quality in the Gowa Regency Regional Health Center - Kusniyanto, Rahayu Eryanti; Aziz, Marlina; Syam, Nurul Fitri Sugiarti (Jurnal Midwifery, 2024)
Introduction Sleep has a major Influence on the mental, emotional, physical health and immune system of baby. Babies who don’t sleep enough are more susceptible to intelligence disorders, difficulty concentrating, weak memory and loss of creativity. The Quality of Baby Sleep can be stimulated by giving baby message. The aim of this research is to determine the effectiveness of baby massage on the quality of sleep in babies at Gowa area Health Center. Method The type of research used in this research is quasi-experimental with one group pre-post test design. The sampling technique used purposive sampling with a total of 30 respondent aged 5-6 months. Result This research shows that before being given a massage, the majority of babies sleep quality was poor, as many as 22 respondents (73,3%), then after being given a message for 3 weeks, there was an increase in sleep quality, where as many as 28 respondents (93,3% had good sleep quality. The Paired T Test result obtained a P Value of 0.000 (P value <0.05). Conclusion There is an effect of baby massage on the quality of Baby sleep.